2018
DOI: 10.4049/jimmunol.1700859
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic Lethality and Host Immunity of RelA-Deficient Mice Are Mediated by Both Apoptosis and Necroptosis

Abstract: In mammalian cells, signaling pathways triggered by TNF can be switched from NF-κB activation to apoptosis and/or necroptosis. The in vivo mechanisms underlying the mutual regulation of these three signaling pathways are poorly understood. In this article, we report that the embryonic lethality of -deficient mice is partially prevented by the deletion of or but it is fully rescued by the combined ablation of and or or by blocking RIP1 kinase activity (RIP1). triple-knockout (TKO) and mice displayed bacterial p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 57 publications
1
22
0
Order By: Relevance
“…In addition to activating the expression of IFN-b, RelA also mediates the expression of genes encoding pro-survival factors. Indeed, RelA was shown to be capable of suppressing apoptotic as well as necroptotic cell death in response to a variety of death-inducing agents (Mitchell et al, 2016;Xu et al, 2018). Our investigation revealed that CHPV engaged both apoptotic and necroptotic pathways for inducing cell death and that RelA restrained death of CHPVinfected cells.…”
Section: Nf-κb Functionsmentioning
confidence: 68%
See 1 more Smart Citation
“…In addition to activating the expression of IFN-b, RelA also mediates the expression of genes encoding pro-survival factors. Indeed, RelA was shown to be capable of suppressing apoptotic as well as necroptotic cell death in response to a variety of death-inducing agents (Mitchell et al, 2016;Xu et al, 2018). Our investigation revealed that CHPV engaged both apoptotic and necroptotic pathways for inducing cell death and that RelA restrained death of CHPVinfected cells.…”
Section: Nf-κb Functionsmentioning
confidence: 68%
“…Canonical NF-kB signaling regulates a diverse range of cellular functions and mediates also the expression of pro-survival factors. Targeted deletion of gene encoding RelA in mice resulted in cellular apoptosis as well as necroptosis and caused embryonic lethality (Beg et al, 1995;Xu et al, 2018). Unavailability of adult mice lacking components of the canonical pathway impeded genetic dissection of NF-kB signaling in the context of virus infections.…”
Section: Introductionmentioning
confidence: 99%
“…S. pneumoniae challenge ( Table 1), but also neutralization of this ligand reversed both liver injury and apoptosis. Necroptosis has been associated with liver injury in certain settings (49,50), and both apoptosis and necroptosis have been attributed to embryonic lethality in RelA knockout mice (51). The necroptosis inhibitor Nec-1s, however, had no effect on liver injury in hepRelA Δ/Δ mice.…”
Section: Discussionmentioning
confidence: 97%
“…While a potential role of NFkB in inhibiting necroptosis was previously suggested [35][36][37] , the molecular regulatory circuits and its significance for necroptosis decision-making remained unknown. Although the anti-inflammatory protein A20 is a prominent NFkB-response gene, its robust TNF-inducibility is not required for inhibiting NFkB 69 , prompting the question of why A20 expression is so highly TNF-inducible.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies investigated NFkB as a potential necroptosis inhibitor [35][36][37][38] , but in certain circumstances, NFkB may even promote necroptosis, e.g. by contributing to TNF production 15 .…”
Section: Introductionmentioning
confidence: 99%